2021
DOI: 10.5815/ijcnis.2021.02.02
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Route Failure Detection Mechanism with Energy Efficient Routing (EER) Protocol in MANET

Abstract: Mobile ad-hoc network (MANET) is a network with two or more number of nodes with restricted energy constraint. The high dynamic nature in MANET attracts needs to consider the energy efficient features in their construct. The routing protocol is an important criterion to be considered for evaluating the performance of the MANET. Energy consumption plays vital role in MANET. Hence designing the scheme that supports energy efficient is much needed for the high dynamic MANET environment concerned. This paper propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…To achieve smart, sustainable energy management, Hemanand et al [19] suggested applying the existing Glow worm Swarm Optimization technique across IoT sensors to detect the devices in need of energy and distribute appropriate energy on a need basis. According to Jayalakshmi et al [20], the routing protocol should be one of the factors examined when gauging a network's efficacy. It was proposed by Gopalakrishnan et al that the security of the system may be enhanced by deploying highly secured cryptographic algorithms on each node in the network.…”
Section: Related Workmentioning
confidence: 99%
“…To achieve smart, sustainable energy management, Hemanand et al [19] suggested applying the existing Glow worm Swarm Optimization technique across IoT sensors to detect the devices in need of energy and distribute appropriate energy on a need basis. According to Jayalakshmi et al [20], the routing protocol should be one of the factors examined when gauging a network's efficacy. It was proposed by Gopalakrishnan et al that the security of the system may be enhanced by deploying highly secured cryptographic algorithms on each node in the network.…”
Section: Related Workmentioning
confidence: 99%
“…Results from simulation and analysis demonstrate the viability of the suggested fixes. The Energy Productive Directing (EER) convention, which depends on compelling course disappointment identification, is proposed in [21]. This research provided an innovative routing method for MANET that minimizes failed communication.…”
Section: Literature Surveymentioning
confidence: 99%
“…Capability recognizes this in this hyper-competitive era, truly a competitive edge to instantly understand and react to hidden trends. Reports project violations for trends of interest in analyzing highway project bid data [8]. Data analysis revealed that bids with higher rates incur significant costs.…”
Section: Big Data Analyticsmentioning
confidence: 99%